Pengolahan Limbah Cair Kupri Khlorid Dengan Ekstrak Abu Secara Sinambung Ditinjau Dar! Segi Kinetika Reaksi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
In industry, washing of Printed Circuit Board(PCB) with hydrochloric acid and hydrogen peroxide produces liquid waste containing a lot of cupric chloride and hydrochloric acid. The allowable cupric ion concentration in waste water is 2 mg/L. Therefore, this liquid waste may not be dumped into the river in order not to pollute the environment. The processing of the liquid waste containing cupric chloric and hydrochloric acid with ash extract was carried out in an upright glass column provided with slanted serrated baffles. The liquid waste and ash extract were fed from the top of the column, while air was bubbled continuosly from the bottom of the reactor. The pH of the effluent was measured every 10 minutes until steady state condition was reached,wich was indicated by constant pH values. The cupric content of the samples was determined using Atomic Absorption Spectrophotometer (AAS). The variables studied were air flow rate, temperature, and molar ratio of potassium carbonate-cupric chloride. The result showed that the reaction was second order with respect to cupric chloride concentration. Within the range of the variables studied, the reaction rate constant was effected by temperature exponentially and logarithmically by potassium carbonates-cupric chloride molar ratio. The favourable process condition was air flow rate of 290 mL/minute, reaction temperature of about 328 K, and 40.67 minutes of residence time. Under this condition, cupric chloride conversion was 99.52% and the liquid left contained cupric ion less than the allowable limit for environment pollution.